فاعلية المسرح في تنمية بعض المفاهيم العلمية لدى عينة من أطفال الرياض(5-6)سنوات دراسة شبه تجريبية في محافظة ريف دمشق (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2013)
تسعى المؤسسات التربوية إلى الاهتمام بالطفولة على اعتبار أنها المرحلة الأهم في تأسيس الكائن البشري،لذا تعمل على استثمار مختلف السبل والوسائل التي تسهم في تنشئة الطفل التنشئة السليمة،ولعل من أبرز هذه الطرائق "مسرح الطفل" الذي يمّكن عبر استغلال إمكاناته الأدبية والفنية الهائلة النهوض بالعملية التعليمية التعلميَة ، لذا هدفت الدراسة الحالية تعرّف فاعلية المسرح في تنمية بعض المفاهيم العلمية لدى طفل الرياض وهي(الحيوانات ونموها،نمو النباتات،الحواس،الحفاظ على الماء،أدوات المهن،المواد ومشتقاتها) وذلك باستخدام أداتي البرنامج المسرحي واختبار مصور للمفاهيم العلمية المكتسبة، وطبقت الدراسة على عينة مكونة من بعض أطفال الرياض في ريف دمشق وقد بلغت العينة التجريبية" 15" طفلاً وطفلةً من روضة بسمة الطفولة والضابطة "15" طفلاً وطفلةً من روضة أشبال الغد وتلخصت أهم النتائج فيما يلي: -  يوجد فرق ذو دلالة إحصائية بين متوسط درجات أطفال المجموعة التجريبية ودرجات أطفال المجموعة الضابطة في الاختبار البعدي لصالح المجموعة التجريبية. - يوجد فرق ذو دلالة إحصائية بين متوسط درجات أطفال المجموعة التجريبية قبل وبعد التطبيق لصالح التطبيق البعدي. ولذا ترى الباحثة ضرورة تفعيل دور المسرح بحيث يصبح طريقة معتمدة بصورة دائمة في مناهج رياض الأطفال وإخضاع معلمات الرياض لدورات تدريبية حول كيفية استخدام المسرح ضمن النشاط اليومي في الروضة. educational institutions are Seeking to pay attention to childhood because it is the most important stage in the establishment of a human being, so they are working on Investment various ways and means which contribute in healthy upbringing of the child, and perhaps the most prominent of these ways, "Children's Theatre", which can be through advancement of its exploitation potential literary and artistic tremendous to raise up of the teaching-learning process, so the current study aimed to know the effectiveness of the stage in the development of some of the scientific concepts at kindergarten children (Animals and  their growth, the growth of plants, the senses, water conservation, professions Tools, materials and their derivatives.) by using tow tools, theatrical program and a photographer test for some scientific concepts. study was applied on a sample of kindergarten children in Damascus countryside. The research sample included the experimental group "15" boys and girls from Basmt Altfolah kindergarten and control group "15" boys and girls from Ashbal Alghad kindergarten, the main findings are summarized as follows: - There is a statistically significant difference between the average scores of children of the experimental group and the control group children grades in the post-test for the experimental group. - There is a statistically significant difference between the average scores of the experimental group children before and after the application for the post. So a researcher see necessity of activating the role of the theater so that it becomes a based way permanently in the kindergarten curriculum and kindergartens teachers should do training sessions on how to use the theater within the daily activity in the kindergarten.